Mengidentifikasi Kendala Pelaksanaan Gerakan Literasi Sekolah Sebagai Upaya Pengembangan Mutu Budaya Literasi Di SMA Negeri Bali Mandara - Sutriyanti, Ni Komang; Dharmawan, I Made (Jurnal Penjaminan Mutu, 2021)
The School Literacy Movement is a government program that focus on developing the quality of literacy culture in schools. SMA Negeri Bali Mandara is one of the schools that is quite intensive in organizing this program. Even since this school was founded, literacy activities have been done as Silent Reading. Reflecting on this, this study selected students of SMA Negeri Bali Mandara as samples to identify obstacles during the implementation of the School Literacy Movement. In this study, several problems were also formulated, namely related to the implementation of the school literacy movement at the SMA Negeri Bali Mandara, various obstacles faced, and the efforts to overcome them. This research was using qualitative research as research methods and with primary and secondary data sources. The technique of determining informants were using purposive sampling technique. Data collection methods was using observation techniques, interviews, document recording, and literature study and using data analysis from Miles and Huberman. The results of this study indicated that, Bali SMA Negeri Bali Mandara had implemented the school literacy movement through three stages, namely habituation stage, development stage, and learning stage. During its implementation, the obstacles faced were identified regarding facilities and infrastructure, human resources, and time allocation. Through this research, it is hoped that the quality of literacy culture can be developed because all obstacles are known and faced.